Megaliths and geology = Megálitos e geologia : Mega-talks 2, 19-20 November 2015 (Redondo, Portugal) - Boaventura, Rui,; Mataloto, Rui,; Pereira, André, (Access archaeology., 2020)
The MegaGeo project, under the direction of the late Rui Boaventura, aimed to analyse the raw material economy in the construction of megalithic tombs in multiple territories, showing the representation of several prehistoric communities that raised them and their relationship with the surrounding areas. Following the meeting of the previous year, it was decided to hold Mega-Talks 2, which brought together national and international experts who have developed work related to Megalithism and Geology, in its various perspectives, from the funerary depositions to the raw material construction of the tombs, as indicators of mobility and interaction with the surrounding physical environment. This title presents contributions from Mega-Talks 2, held in Redondo, Portugal, on 19-20 November 2015.